The low Female Literacy Trends: A Critical Challenge of Human Development in Pakistan (Major Obstacles and Way Forward) - Tagar, Hamzo Khan; Abro, Lahoot Tariq; Chandani, Alishah Mukhtar; Khoso, Zamir Ahmed; Sohoo, Muhammed Nawaz (Archives of Business Research, 2019)
The study examines the current status of female literacy and its nexus with development in the context of Pakistan where more than sixty percent females are illiterate and illiterate females are more than that in its rural and far-flung areas. The study examines the key obstacles in the system and discusses possibilities to improve female literacy rate with enhancement in quality of education. It finds that development allocation fared poorly in the past for female education and human development in the region. The lower female literacy rate strengthens feudalism and contributing to unskilled- or semi-skilled women labour force which is spreading poverty and inequality in the country in the global age of the twenty-first Century. Above mentioned issues direly need to adopt an innovative approach to tackle all obstacles in decent manners and through coherent development planning, policies, and practices. It is also concluded that low female literacy trends affect inversely on growth and economic development of the region, so to bring quality educations for female literacy is need of the hour for sustainable economic growth and development.